The Husband's Obligation to Provide for His Wife in Ṣīgat Taklīk Ṭalāk: Analysis of the Madhhab of Jurisprudence - Maloko, M. Thahir; Darsa, Muh Ikhwan; Cahyani, A. Intan (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2022)
This article analyzes the husband's subsistence obligations to his wife in divorce proceedings from the point of view of different schools of fiqh. Livelihood is a fundamental right for women in Islam, and this provision has significant implications for divorce situations. The main purpose of this study is to analyze the various schools of thought regarding the husband's subsistence obligations towards his wife during and after the divorce process. The research method used is a comparative analysis of the views of the four major madhhabs of Jurisprudence: Hanafi, Maliki, al-Shafi'i and Hanbali. This article discusses various madhhabs and interpretations regarding whether the husband's obligation to provide for his wife after the declaration of divorce. The results of the analysis show that there are significant differences between madhhab scholars in understanding the husband's obligation to provide in the context of talaq. There are those who argue that this obligation to provide for a certain period after the divorce statement, while there are also those who argue that the obligation to pay income will end by itself. This article aims to provide a deeper understanding of the different views of madhhab scholars on the obligation to provide for wives and husbands during the taklīk ṭalāk period. In addition, this article provides insight into how these traditional views can be adapted to changing social and legal circumstances over time.